N-palmitoylethanolamide in the anterior cingulate cortex attenuates inflammatory pain behaviour indirectly via a CB1 receptor-mediated mechanism. Issue 12 (December 2016) - Okine, Bright N.; Madasu, Manish K.; McGowan, Fiona; Prendergast, Charles; Gaspar, Jessica C.; Harhen, Brendan; Roche, Michelle; Finn, David P.
Abstract : Abstract: The neural substrates and mechanisms mediating the antinociceptive effects of the endogenous bioactive lipid, N -palmitoylethanolamide (PEA), require further investigation. We investigated the effects of exogenous PEA administration into the anterior cingulate cortex (ACC), an important brain region linked with cognitive and affective modulation of pain, on formalin-evoked nociceptive behaviour in rats. Potential involvement of peroxisome proliferator-activated receptor isoforms (PPAR) α and γ or endocannabinoid-mediated entourage effects at cannabinoid1 (CB1 ) receptors or transient receptor potential subfamily V member 1 (TRPV1) in mediating the effects of PEA was also investigated. Intra-ACC administration of PEA significantly attenuated the first and early second phases of formalin-evoked nociceptive behaviour. This effect was attenuated by the CB1 receptor antagonist AM251, but not by the PPARα antagonist GW6471, the PPARγ antagonist GW9662, or the TRPV1 antagonist 5′-iodo resiniferatoxin. All antagonists, administered alone, significantly reduced formalin-evoked nociceptive behaviour, suggesting facilitatory/permissive roles for these receptors in the ACC in inflammatory pain. Post-mortem tissue analysis revealed a strong trend for increased levels of the endocannabinoid anandamide in the ACC of rats that received intra-ACC PEA. Expression of c-Fos, a marker of neuronal activity, was significantly reduced in the basolateral nucleus of the amygdala, but not in the central nucleus of the amygdala, the rostral ventromedial medulla or the dorsal horn of the spinal cord. In conclusion, these data indicate that PEA in the ACC can reduce inflammatory pain-related behaviour, possibly via AEA-induced activation of CB1 receptors and associated modulation of neuronal activity in the basolateral amygdala. Abstract : Supplemental Digital Content is Available in the Text. N -palmitoylethanolamide in the ACC reduces inflammatory pain via anandamide-induced activation of CB1 receptors, with associated modulation of neuronal activity in the amygdala.